Pre-operative pediatric cardiac surgery: enema Versus not enema - Prendin, Angela; Sansone, Vincenza; Brugnaro, Luca; de Barbieri, Ilaria (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: There is evidence in adult literature that the enema in the preoperative of thoracic surgery can be dismissed without disadvantage. However, there is a gap of articles about enema in childhood for thoracic surgeries. The aim of the work is to investigate whether the administration of enema in the preparation for cardiac surgery, the use of different analgosedation drugs and the Extracorporeal Circulation influence the children’s intestinal motility in the post-operative period. Methods: A retrospective study was carried out comparing the data between users subjected to saline solution enema, originating from the U.O.C. of Pediatric Cardiology and Pediatric Cardiac Surgery and Congenital Heart Disease and users not subjected to such procedure, coming from the U.O.S.D. Pediatric Intensive Care. The data collected will evaluate the intestinal motility in the post-operative cardiac surgery. Results: The following three variables were analyzed: interval of post-operative evacuation days (mean 2.14, median 2.00, standard deviation 1.525 in non-enema children; mean 2.76, median 2.00, standard deviation 1.318 in enema children), administered analgosedation drugs and use of Extracorporeal Circulation - for which the Pearson Test was used. A sampling bias is also reported from the analysis of the data. The study did not show a statistical significance correlates the variables analyzed to intestinal motility in post-operative period. Conclusion: The sampling bias emerged could reflect the diversity of the catchment area in the two Wards. The study - in agreement with the literature concerning the adult user - proves that the practice of enema evacuation pre-operative cardiac surgery in the pediatric user is unnecessary and does not influence intestinal transit in the post-operative period.